Analisis Kebijakan Eksplorasi Komuditi Pertanian Berbasis Local Wisdom dalam Mendorong Perkembangan Ekonomi Syariah di Kabupaten Pulang Pisau: Policy Analysis of Exploration of Agricultural Commodities Based on Local Wisdom in Encouraging the Development of Sharia Economy in Pulang Pisau Regency - Jariah, Ainun; Junaidi, Junaidi; Ariyadi, Ariyadi; Bawi, Marga Tri Nuche Wisne Firdana; Sutrisno, Edi (Anterior Jurnal, 2025)
Technological advances are currently changing the direction of policies, including in the agricultural sector so that they are based on technology and information. The goal is of course to provide efficiency and effectiveness in the results obtained. However, in the agricultural process in Pulang Pisau district, this is not fully applicable, as evidenced by the Food Estate policy which experiences various obstacles. Therefore, this is a special concern when it is associated with the success of agriculture based on the local wisdom of the Dayak tribe. So the urgency of this research is that various obstacles occur in the leading agricultural commodities in Pulang Pisau Regency that have been carried out. The purpose of this research is to find out how the Exploration Policy of Agricultural Commodities Based on Local Wisdom in Encouraging the Development of Sharia Economy in Pulang Pisau Regency. A qualitative method with a descriptive approach is the method of this research. In the findings of the research, it is illustrated that the agricultural sector has had an extraordinary impact on improving the economy for the lives of the people in Pulang Pisau Regency, but there are still various obstacles including the availability of irrigation governance is not completely good, the resources owned are still minimal, the transfer of farming commodities, the transfer of land functions, and the absorption of crop yields are not by the desired expectations and in economic development is still in the conventional system.